Rapid vascularization of starchâ poly(caprolactone) in vivo by outgrowth endothelial cells in co-culture with primary osteoblasts - Ghanaati, Shahram (2011)
The successful integration of in vitro-generated tissues is dependent on adequate vascularization in vivo. Human outgrowth endothelial cells (OECs) isolated from the mononuclear cell fraction of peripheral blood represent a potent population of circulating endothelial progenitors that could provide a cell source for rapid anastomosis and scaffold vascularization. Our previous work with these cells in co-culture with primary human osteoblasts has demonstrated their potential to form perfused vascular structures within a starch–poly(caprolactone) biomaterial in vivo. In the present study, we demonstrate the ability of OECs to form perfused vascular structures as early as 48 h following subcutaneous implantation of the biomaterial in vivo. The number of OECderived vessels increased throughout the study, an effect that was independent of the OEC donor. This finding of rapid and thorough OEC-mediated scaffold vascularization demonstrates the great potential for OEC-based strategies to promote vascularization in tissue engineering. OECs have the potential to contribute to host-derived scaffold vascularization, and formed vascular structures at a similar density as those arising from the host. Additionally, immunohistochemical evidence demonstrated the close interaction between OECs and the co-cultured osteoblasts. In addition to the known paracrine activity osteoblasts have in modulating angiogenesis of co-cultured OECs, we demonstrate the potential of osteoblasts to provide additional structural support for OEC-derived vessels, perhaps acting in a pericyte-like role.